(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In the scientific work, in order to effectively use local raw materials, research was conducted on the physical and mechanical properties of two-layer knitted fabrics of a new structure made of polyacrylonitrile yarn.